2009
DOI: 10.1246/bcsj.82.1003
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome c551 Is a Mediator of Electron Transfer between Copper-Containing Nitrite Reductase and Azurin in a Denitrifying Bacterium, Achromobacter xylosoxidans

Abstract: Cu-containing nitrite reductase from a denitrifying bacterium, Achromobacter xylosoxidans GIFU1051 (the organism formerly known as Alcaligenes xylosoxidans), can accept an electron from three possible electron donors (cytochrome c551 and two azurins). We have kinetically demonstrated that cytochrome c551 functions as a mediator in the electron flow processes between the enzyme and two azurins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…An important aspect of this topic relates to which redox partners carry out direct electron transfer to neisserial NirK. Although in vitro studies have identified both azurins (members of the cupredoxin family) and c -type heme cytochromes as electron donors to other members of the blue, copper - containing nitrite reductase (CuNIR) family [60] , [61] , only rarely have the physiological contributions been addressed in vivo . Although both N. meningitidis and N. gonorrhoeae express a lipoprotein form of azurin termed Laz, it has been reported that Laz is nonessential for growth under either aerobic or anerobic conditions (in the presence of nitrite) [62] .…”
Section: Discussionmentioning
confidence: 99%
“…An important aspect of this topic relates to which redox partners carry out direct electron transfer to neisserial NirK. Although in vitro studies have identified both azurins (members of the cupredoxin family) and c -type heme cytochromes as electron donors to other members of the blue, copper - containing nitrite reductase (CuNIR) family [60] , [61] , only rarely have the physiological contributions been addressed in vivo . Although both N. meningitidis and N. gonorrhoeae express a lipoprotein form of azurin termed Laz, it has been reported that Laz is nonessential for growth under either aerobic or anerobic conditions (in the presence of nitrite) [62] .…”
Section: Discussionmentioning
confidence: 99%
“…Each monomer of typical CuNiR contains two copper sites: Type 1 Cu (T1Cu) with a Cys–Met–His 2 ligand set and Type 2 Cu (T2Cu) with a His 3 ligand set ( 9–13 ). The T1Cu site accepts an electron from c -type cytochromes ( 14 , 15 ) or blue copper proteins ( 6 , 16 , 17 ), when CuNiR and the donor protein form a transient electron transfer (ET) complex. The received electron are transferred to the T2Cu site, the catalytic centre, through a Cys–His pathway.…”
mentioning
confidence: 99%
“…CuNIR typically has a homotrimeric structure containing one type 1 (T1Cu) and one type 2 Cu (T2Cu) site per monomer. The T1Cu atom is coordinated by four amino acid residues (two histidine residues, cysteine and methionine) and functions as a receptor site for the electron supplied by an electron-donor protein such as c-type heme-containing cytochrome (8,9) or blue-copper proteins (10,11). The T2Cu site is a catalytic centre composed of three histidine residues and an axial ligand water molecule.…”
mentioning
confidence: 99%